In Search of George Scott: Jack of All Trades, Motion Picture Pioneer, World Explorer - Clarke, Robert (Ontario History)

(untitled) (The Ontario Historical Society, 2020)
In the first decade of the twentieth century George Scott established a motion picture firm in Toronto. He filmed the “Great Toronto Fire” of 1904, attempted to show movies on Toronto Island, and took time out to open a “theatorium” in Peterborough, Ont., in 1907. Scott worked in the budding filmmaking industry in London, England, in Europe, and in Toronto, New York, and Hollywood. He also shot film around the world: from the South Pacific, Australia, Southeast Asia, and Japan to British East Africa. He died in Los Angeles in January 1929. Scott had a motion picture career of global proportions, but he is almost entirely known only for having produced one of the first films shot in Toronto. This article traces his life before and after his time in Toronto.